Progress of participatory management: reconnaissance results - International Irrigation Management Institute; Agrarian Research and Training Institute, Sri Lanka (International Irrigation Management Institute, 1993)
This report is a product of the Monitoring and Evaluation of the Participatory Irrigation System Management Policy being carried out jointly by IIMI and ARTI under the auspices of the Ministry of Forestry, Irrigation and Mahaweli Development. The work is funded by Technical Assistance no. 1705 SRI, from the Asian Development Bank.